PENINGKATAN KOMPETENSI PESERTA DIDIK MADRASAH MELALUI PENDIDIKAN KARAKTER BERBASIS PESANTREN - Salim, Ahmad (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2012)
Abstract: An issue of character education in Indonesia has been widely discussed since the character education movement launched on May 2, 2010. Character education has become an important part of the national education system and become preventive cure on various social ills. Islamic education has some appropriate terminologies used in the character learning approach, such as: tilÃ¢wah, taâlÃ®mâ, tarbiyah, taâdÃ®b, tazkiyah dan tadlrÃ®b. Recitations (tilÃ¢wahi) is related to the ability to read; taâlim related to the development of intelligence (intellectual quotient); tarbiyah regarding care and affection instinctively, tadib associated with the development of emotional intelligence (emotional quotient); tazkiyah related to the development of spiritual intelligence (spiritual quotient), and tadlrib associated with physical intelligence or skills (physical quotient or adversity quotient). The integration of character education in all subjects at the school is regarded as one way to improve the competence of cognitive, affective and psychomotor of learners equally. This study discusses the system of Islamic boarding schools with the characteristics, clerics, mosques and dormitories to be an alternative solution to implement character education in such effective, consistent and sustainable ways. The system of Pesantren will optimize the educators role as an educator, conservator, innovators, transformers, organizers and all stakeholders of madrasah so that its value or characters can be internalized and implemented by students optimally.